1995
DOI: 10.1016/s1078-5884(05)80218-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of vein graft failure: A review

Abstract: Vein bypass grafting is an integral component of cardiovascular surgical practice for both arterial and venous diseases. However, many of these grafts will eventually fail due to either intrinsic or extrinsic causes. This review examines the current understanding and knowledge of venous histology, vein graft pathology and the associated endothelial and smooth muscle cell physiology and pharmacology. In addition, the status of research on the therapeutic control of vein graft intimal hyperplasia and accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
167
0
8

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(182 citation statements)
references
References 114 publications
1
167
0
8
Order By: Relevance
“…1,2 Development of intimal hyperplasia, through smooth muscle cell (SMC) proliferation and migration, 3,4 diminishes lumen diameter and, in association with thrombosis and atherosclerosis, can lead to total vein graft occlusion. 1,2 Pathological vein graft remodeling also includes medial and adventitial hypertrophy and sclerosis, whose precise consequences remain to be defined. 5 Previous studies 6 -10 have shown that SMC proliferation and migration and general tissue reshaping depend on the activity of matrixdegrading enzymes called matrix metalloproteinase (MMP)-2 and MMP-9, known also as gelatinase A and B.…”
mentioning
confidence: 99%
“…1,2 Development of intimal hyperplasia, through smooth muscle cell (SMC) proliferation and migration, 3,4 diminishes lumen diameter and, in association with thrombosis and atherosclerosis, can lead to total vein graft occlusion. 1,2 Pathological vein graft remodeling also includes medial and adventitial hypertrophy and sclerosis, whose precise consequences remain to be defined. 5 Previous studies 6 -10 have shown that SMC proliferation and migration and general tissue reshaping depend on the activity of matrixdegrading enzymes called matrix metalloproteinase (MMP)-2 and MMP-9, known also as gelatinase A and B.…”
mentioning
confidence: 99%
“…En los casos más avanzados, esta proliferación puede producir una estenosis en el injerto que puede poner en peligro la permeabilidad del procedimiento. Todos los injertos venosos desarrollan cierto grado de hiperplasia intimal durante el seguimiento, pero aún se desconoce por qué en algunos casos evoluciona hasta producir una estenosis significativa (29)(30)(31)(32) . La figura 4 muestra la reestenosis de un injerto venoso femoro-poplíteo secundario a hiperplasia intimal.…”
Section: Fracaso Intermediounclassified
“…The high incidence of graft failure has led to the evolution of graft surveillance programs to detect 'failing' grafts and research has focussed on means to control the development of intimal hyperplasia. [22] …”
Section: History Of Surgical Revascularizationmentioning
confidence: 99%